O JOGO EM JOGO: EDUCAÇÃO DAS RELAÇÕES ÉTNICO-RACIAIS E A COMPREENSÃO DAS REGRAS POR CRIANÇAS QUILOMBOLAS - VOLSKI, VERÔNICA (2015)
This study presents the knowledge of African and afro-brazilian culture, according to Law 10.639 / 2003, and also the understanding, execution and drawing up rules, by 'quilombolas' children. The playing rule was chosen as a study tool, from the use of African and afro-brazilian games. Thus, it was observed that the game rules feature, at the same time, knowledge of the culture and the development of awareness and practice of social rules. From the analysis of production related to the theme of study, it was pointed to the lack of research within the traditional game, especially African and afo-brazilian and 'quilombola', as well as studies on the playing field in social and moral perspective. The clinical method of Piaget was used as a methodological strategy, starting from open conversations to open situations (game). Were analyzed one hundred fifty-three children in a school of boys and girls of the community 'Quilomobola Invernada Paiol de Telha-PR'. The analyses were performed in two parts: the first with the games "What is Africa" and "What is Capoeira" and the second with 'Matacuzana' and 'Mancala' games (in the second analysis focused in the twenty-two 'Quilombola' children who participated in the games). As a result it was found that children have a limited and superficial knowledge of the contents involving African history and afro-brazilian culture. The silencing by the 'Quilombola' kids was evident. Regarding the understanding of the rules by the 'Quilombola' kids, it was found that for the practice of the rules, most are in the egocentric stage (Matacuzana game) and in the cooperation stage (Mancala game), according to Piaget (1994). For the consciousness of the rules, most are in the second stage (for both games) glimpsing the rule as sacred, imposed by the adult and unchanging. Often they performed the rules, assimilating and applying the game rules during the practices. Obeying the rules and not proposing new ways to play, which suggests that the use of the rule is related to the heteronomous character of their actions. This research points out, therefore, the importance of teaching knowledge about multicultural work in the school as well as the way that children understand the rules and how it infers social relations between subjects.